Atom Probe Tomography (APT) and Its Application in Ore Deposits - Peng TAO; Shiwen XIE; Tao LONG; Mingzhu MA; Xiaochao CHE (Yankuang ceshi)
Atom Probe Tomography (APT) is a test analysis technique that provides quantitative three-dimensional element and isotope analysis at subnanometer resolution, with extremely high spatial resolution and low detection limits[13]. Compared with traditional geological analysis techniques, APT has unique technical advantages, which can be used to analyze the elemental composition of minerals <0.0007μm3 in volume[14], reveal the complexity of mineral composition at the nanoscale, and provide a new understanding of the geological evolution process.　　APT has been in development for over 50 years, and continuous technological advancements have led to its wider application range. At the beginning of APT design, it was only used for conductive materials. From the end of the 20th century to the beginning of the 21st century, the application of laser pulse mode enabled APT to be applied to semiconductors and insulating materials[15-19], and the application of Local Electrode TM Atom Probe (LEAP) improved several key parameters such as the data acquisition rate and mass resolution of APT by several orders of magnitude[20]. At present, most of the geological application work of APT is carried out by LEAP in laser-assisted mode[13]. In recent years, the unique technical advantages of APT have attracted increasing attention in geological research, and their advantages in ore deposit research have become more prominent. Some important research results have been published[21-31]. However, on the whole, its application in ore deposits and even geology is still in its infancy.　　The development history, basic principle, selection method of area of interest and needle tip sample preparation of APT are briefly introduced in this paper. Based on this, representative application achievements of APT in ore deposit research by domestic and foreign scholars in recent years are collected and summarized. In ore deposit research, APT is mainly applied in three aspects: the occurrence states of ore-forming elements, nanoscale inclusions, and stable isotope composition[21-31]. At present, most research results focus on the analysis of the occurrence status of ore-forming elements, especially pyrite or other minerals with simple chemical composition related to gold deposits. APT has successfully revealed three main occurrence states of ore-forming elements on the atomic scale: uniform distribution, nanoparticle and enrichment at low angle grain boundaries and dislocations[21-25]. For example, gold can be uniformly distributed in the form of dispersed lattice bound gold in the arsenic-rich overgrowth rim of pyrite[21], and can form nanoclusters of different sizes in arsenopyrite[22]. It can also host in the low angle boundary of pyrite related to deformation[24]. In terms of nano inclusions and stable isotope composition, the research mainly focuses on pyrite nano fluid inclusions and S isotopes[26-31]. For example, nano telluride inclusions along pyrite fractures in low-sulfidation type epithermal Au-Ag-Te deposit[26] and the method for obtaining quantitative δ34S measurement value from APT datasets of pyrite[29]. The relevant results are shown in Fig.E.1. So far, the applications of APT in ore deposits research have mainly focused on the occurrence state of ore-forming elements, achieving three-dimensional visualization of atomic scale element distribution that was previously unimaginable, providing a new perspective for people to understand and explain the ore-forming process. In terms of nano inclusions and stable isotope composition, although the applications of APT are not as rich as the former, some important new understandings have been obtained, showing a good application prospect.　　While APT is rapidly developing in the field of ore deposits, there are still many problems to be solved in its practical application. For example, the extremely small sample volume, time-consuming selection of specific areas, the background noise carried by the mass spectrometry itself, the correct interpretation of complex spectral peaks, and the accuracy of data three-dimensional reconstruction. However, it is foreseeable that with the continuous progress of technology, APT will become more popular and easier to use, increasing numbers of deposit researchers will pay attention to APT, and more ore deposit samples with complex types, structures and chemical compositions will apply this technology for in-depth research, which may change or even completely subvert our understanding of some basic scientific problems in ore deposits.